Well-Being Washing: Illusory Employee Care in an Organisation - Katarzyna Mikołajczyk (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2025)
Aim: The article explores the issue of well-being washing, identifying its indicators and impact on employees and organizations, while outlining the key components of effective organizational well-being strategies.